2011
DOI: 10.1007/s00441-011-1209-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TrkB and BDNF in human cochlea—an immunohistochemical study

Abstract: Surgical human cochlear specimens were obtained during the removal of large posterior cranial fossa meningioma by a transcochlear approach in which the cochlea was removed for maximal exposure of the tumor and protection of important structures, such as the brainstem, cranial nerves, and pivotal blood vessels. The cochlear tissue was fixed and cryo-sectioned for tyrosine kinase receptor B (TrkB) and brain-derived neurotrophic factor (BDNF) immunohistochemistry. TrkB receptor protein was expressed in both neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 34 publications
(41 reference statements)
2
35
2
Order By: Relevance
“…Earlier research from our group using fetal human cochleae showed BDNF immuno-staining at GW 12 but not in previous stages (Pechriggl et al 2015). In addition, BDNF localization was not observed in immuno-stained cochlear sections from human adults (Liu et al 2011). These findings are not in line with our present data, where ISH clearly demonstrated BDNF expression in both fetuses (GW 9-12) and adults.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Earlier research from our group using fetal human cochleae showed BDNF immuno-staining at GW 12 but not in previous stages (Pechriggl et al 2015). In addition, BDNF localization was not observed in immuno-stained cochlear sections from human adults (Liu et al 2011). These findings are not in line with our present data, where ISH clearly demonstrated BDNF expression in both fetuses (GW 9-12) and adults.…”
Section: Discussioncontrasting
confidence: 99%
“…TrkB expression was also evident in the spiral ganglion cells of the developing inner ear at GW 11. This finding parallels previous immuno-histochemical examinations of adult human cochleae revealing TrkB expression being localized in spiral ganglion neurons (Liu et al 2011).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The specificity of the polyclonal antibody for p75 NTR was also verified in previous Western blotting (Weskamp and Reichardt 1991;Bitsche et al 2011). Here, we used TrkB to demark the neurons because our previous study has proved that TrkB is a reliable marker for human spiral ganglion neurons and its specificity was clarified in our report (Liu et al 2011). The results of the negative staining in our antibody control ruled out the possibility of a direct staining by reagents other than the primary p75 NTR antibodies.…”
Section: Tissue Preservation and Antibody Specificitymentioning
confidence: 82%
“…Nevertheless, these studies have been mostly carried out in animals and a few in human fetuses (Vega et al 1999). Even though some data on the expression of neurotrophic substances in adult human cochlea have been achieved (Liu et al 2011), our picture in humans is still far from complete.…”
Section: Introductionmentioning
confidence: 99%